Experimental Investigation of Progressive Collapse of Prestressed Concrete Frames after the Loss of Middle Column - Tao Yang; Wanqing Chen; Zhongqing Han (Advances in Civil Engineering)
Accidental loads such as explosion and vehicle impact could lead to failure of one or several load-bearing members in the structures, which is likely to trigger disproportionate progressive collapse of overall structures. Prestressed concrete (PC) frame structures are usually at great risk of collapse once load-bearing members fail, because the members in PC frame structures are usually subjected to much more load than those in common reinforced concrete (RC) frame structures. To investigate the progressive collapse behaviors of PC frame structures, five one-fourth reduced scaled frame substructures were fabricated and collapse tests were conducted on them. Influence of span-to-depth ratios of frame beams and prestress action modes on the collapse performance of PC frame structures was discussed. Experimental results indicated that PC frame substructures with different prestress action modes, including bonded prestress and unbonded prestress, presented different collapse resistance capabilities and deformability. Tensile force increment of the unbonded prestressing strands almost linearly increased with the vertical displacement of the failed middle column. Catenary action is one of the most important mechanisms in resisting structural collapse. Prestressing strands and longitudinal reinforcing bars in the frame beams benefited the formation and maintaining of catenary action. The ultimate deformability of the PC frame structures was tightly connected with the fracture of prestressing strand. In addition, a calculation method of dynamic increase factors (DIFs) suitable for PC frame structures was developed, which can be used to revise the design collapse load when static collapse analysis is conducted by the alternative path method. The DIFs of the five substructures were discussed on the basis of the proposed method; it revealed that the DIFs corresponding to the first peak loads and the ultimate failure loads for the PC frame substructures were less than 1.49 and 1.83, respectively.